IMPLEMENTASI PEMBUATANSERVER VOIP MENGGUNAKAN TRIXBOX: VOIP SERVER DEVELOPMENT IMPLEMENTATION USING TRIXBOX - Julius Panda Putra Naibaho (Universitas Papua, 2015)
VoIP is a technology that allows telephone calls to be made over computer networks like the Internet. VoIPconverts analog voice signals into digital data packets and supports real-time, two-way transmission ofconversations using Internet Protocol (IP). VoIP calls can be made on the Internet using a VoIP service providerand standard computer audio systems. Alternatively, some service providers support VoIP through ordinarytelephones that use special adapters to connect to a home computer network. Trixbox is a PBX software that isbased on Asterisk. With Trixbox, you can place your phone calls using VoIP technology. If you use Ozeki PhoneSystem XE you can build an efficient application with VoIP support. In this guide you can learn how to connectOzeki Phone System XE to Trixbox.